Inequality Comparisons with Ordinal Data - Stephen P. Jenkins (Institute of Labor Economics (IZA), 2019)
Non-intersection of appropriately-defined Generalized Lorenz (GL) curves is equivalent to a unanimous ranking of distributions of ordinal data by all Cowell and Flachaire (Economica 2017) indices of inequality and by a new index based on GL curve areas. Comparisons of life satisfaction distributions for six countries reveal a substantial number of unanimous inequality rankings.
Keywords: D31; D63; I31; 330; inequality; ordinal data; subjective well-being; life satisfaction; World Values Survey